Hereditary tyrosinemia type 1 in an infant with multiple congenital defects - H. A. Sarkisyan; S. V. Cherkasova; A. A. Fadeeva; A. S. Yarushnikova; Yu. S. Piliuzina; A. B. Smolyannikova; E. I. Shabelnikova; L. M. Makarova; M. A. Ovsyannikova; L. A. Levchenko; T. G. Demyanova (Лечащий Врач)
Hereditary tyrosinemia type 1 or hepatorenal tyrosinemia is a severe orphan autosomal-recessive disorder of tyrosine metabolism caused by a deficiency of the enzyme fumarylacetoacetate hydrolase (FAH). The disease is diagnosed in approximately 1:100 000-1:120 000 cases of live births, and in certain regions (such as the Chechen Republic in Russian Federation) the estimated frequency of diagnosis can be significantly higher. In hereditary tyrosinemia type 1, blood levels of tyrosine, succinylacetone and other toxic metabolites are increased, which results in the accumulation of the toxic metabolites in target organs causingliver damage with progressive development of liver failure and liver cirrhosis, damage to the renal tubules resulting in Fanconi syndrome and hypophosphatemic rickets, and central nervous system. In some patients, myocardium could be involved in the pathological process, resulting in the development of hypertrophic cardiomyopathy. The disease presents a great challenge for differential diagnosis due to its polyorganic nature and frequent combination with other hereditary disorders. The modern treatment of hereditary tyrosinemia type 1 includes an elimination-based diet and pathogenetic drug therapy. The potential of genetic engineering methods in target therapy of hereditary tyrosinemia type 1 is being actively researched. Within the article if presented a case of early onset hereditary tyrosinemia type 1 in an infant with multiple congenital defects of central nervous system, including Dandy – Walker syndrome, and congenital defects of maxillofacial area, with signs of an immunodeficiency state and a severe generalized recurring infectious process involving poly-resistant mixed flora. The dynamic changes of neurologic signs are provided for the first year of life of the patient receiving the pathogenetic therapy for the main disease. Laboratory findings are provided, showing the dynamic changes in liver function of the patient.